القناصل في ظل الدولة العثمانية ودورهم في بلاد الشام 1247ه ــ 1333ه ، 1831م ــ 1914م - البودي مازن (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
يتناول البحث مسألة القناصل في بلاد الشام في العقود الاخيرة من عمر السلطنة العثمانية، من خلال محاولة فهم معنى عمل القناصل، والأجواء التي رافقت دخولهم الى دمشق، وطرق تعيينهم، ومن ثم صداماتهم فيما بينهم طمعا بالحصول على الحصة الاكبر من خيرات السلطنة، ويشير البحث الى وكلاء القناصل ومرافقيهم من أهالي السلطنة، ويحاول فهم العلاقة بين القناصل والولاة وتداخلها، ودورهم في الحياة العامة وتجاوز صلاحياتهم، والأهم من ذلك كله يبحث عن دور القناصل في تسيير الحركة التجارية والتحكم بها في بلاد الشام من المرافئ الى الأسواق. This research deals with the issue of consuls in the Levant in the last decades of the Ottoman Empire, by trying to understand the meaning of the work of the consuls, and the atmosphere that accompanied the entry into Damascus, and methods of appointment, and then the differences among them the hope of obtaining the largest share of the bounties of the Sultanate. The research indicates agents’ consuls and their escorts from the people of the Sultanate, and trying to understand the relationship between the consuls, governors and overlap, and their role in public life and exceeded their powers, and most of all looking for the role of consuls in the conduct of trade movement and control in the Levant from ports to markets.